PENERAPAN ASKEP DENGAN GANGGUAN SISTEM REPRODUKSI CA SERVIKS DALAM PEMENUHAN KEBUTUHAN RASA NYAMAN (NYERI) Application Of Nursing Care With Servical Cancer in Fulfilling Comfortable Needs (Pain) - Zulfia Samiun (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2019)
AbstractBackground: Cervical cancer is a leading cause of death among women worldwide. It is estimated that 274,000 deaths occur each year due to this preventable disease. According to the World Health Organization (2013) quoted from Rachmawati (2014), deaths from breast cancer and cervical cancer in 2011 were 273,500. Deaths and in 2010 totaled 247,000, in Indonesia every year the number of patients with cervical cancer according to the Indonesian Cervical Cancer Care Foundation (2012), in Indonesia each year the number of patients with cervical cancer is very high, 15,000 cases. This was stated to be equivalent to 40 women suffering from cervical cancer and 20 of them died. In 2030, in Indonesia the number of patients with cervical cancer is expected to experience a 7-fold increase.Purpose: to carry out nursing care for Ny